The Triple Helix Framework of Government Leadership for Regional Tourism Development - Sadat, Anwar; Nastia (Universitas Pancasakti Tegal, 2023)
The potential of the tourism sector offers opportunities to increase the competitiveness of a region. This prospect lies in implementing the leadership framework of the Triple Helix government. This research aims to establish the correlation between tourism's latent potential and collaborative synergies between local government, industry stakeholders, and the academic community at universities, all in an effort to drive the evolution of the tourism sector. The focus of this research is on leadership and the real results that come from government, embodied in the Triple Helix policy. This study uses a qualitative method to assess and analyze the Triple Helix. This approach includes analysis of underlying causal factors, evaluation of results, and analysis of interactive models. The results of the study show that the leadership aspect in the context of the Triple Helix government framework has not yet reached its peak, especially in the tourism industry, including (a) increasing the value of superior products, (b) regional income, (c) employment, (d) providing a tourism platform that is recognized in education, (e) offering unique memorabilia, and (f) strengthening the brand identity of the designated Tourism Area. However, this effort shows a suboptimal level of performance due to several deficiencies, covering issues such as (a) formal and informal institutions, (b) the world of work, (c) the domain of production technology, (d) the paradigm of corporate governance ( management), (e) access to market outlets, and (f) infrastructure.